Math, asked by mkhtrali, 10 months ago

the length of one side of right triangle exceeds the length of the other by 3cm if the hypotenuse is 15 cm then the length of the sides of the triangle​

Answers

Answered by pandaXop
13

Other Sides = 12 & 9 cm

Step-by-step explanation:

Given:

  • Length of one side of right angled triangle exceeds other side by 3 cm.
  • Measure of hypotenuse of triangle is 15 cm.

To Find:

  • Measure of all sides of triangle ?

Solution: Let the length of one side be x cm. Therefore,

Length of another side = 3 more than x

Length of another side = (x + 3) cm

Since, it is right angled triangle so let's assume that

  • Perpendicular = (x + 3) cm
  • Base = x cm
  • Hypotenuse = 15 cm

By using Pythagoras theorem in this ∆

= Base² + Perpendicular²

\implies{\rm } 15² = + (x + 3)²

\implies{\rm } 225 = + + + 2x3

\implies{\rm } 225 = 2x² + 9 + 6x

\implies{\rm } 225 9 = 2x² + 6x

\implies{\rm } 216 = 2(x² + 3x)

\implies{\rm } 216/2 = + 3x

\implies{\rm } 108 = + 3x

Now, solving the above equation by middle term splitting method.

x² + 3x – 108 = 0

x² + 12x – 9x – 108

x(x + 12) – 9 (x + 12)

(x + 12) or (x – 9)

x + 12 = 0 or x – 9 = 0

x = – 12 or x = 9

Since, length cannot be negative so we have to take positive value of x i.e 9.

• Base is x = 9 cm

• Perpendicular is x + 3 = 9 + 3 = 12 cm

Answered by Rudranil420
39

Answer:

Question

The length of one side of right triangle exceeds the length of the other by 3cm if the hypotenuse is 15 cm then the length of the sides of the triangle.

Given

Length of one side of right angled triangle exceeds other side by 3 cm.

Measure of hypotenuse of triangle is 15 cm.

To Find

Measure of all sides of triangle ?

Solution

Let the length of one side be x cm.

Therefore,

Length of another side = 3 more than x

Length of another side = (x + 3) cm

Hence, it is right angled triangle so let's assume that

Perpendicular = (x + 3) cm

Base = x cm

Hypotenuse = 15 cm

By using Pythagoras theorem in this ,

H²=Base²+Perpendicular²

=> 15² = x² + (x + 3)²

=> 225 = x² + x² + 3² + 2.x.3

=> 225 = 2x² + 9 + 6x

=> 225 – 9 = 2x² + 6x

=> 216 = 2(x² + 3x)

=> 216/2 = x² + 3x

=> 108 = x² + 3x

Now, we have to solve the above equation with the help of middle term splitting method.

=> x² + 3x – 108 = 0

=> x² + 12x – 9x – 108 = 0

=> x(x + 12) – 9 (x + 12) = 0

=> (x + 12) (x – 9) = 0

=> x + 12 = 0 | x – 9 = 0

=> x = – 12 | x = 9

x = 9Since, length cannot be negative so we have to take positive value of x i.e 9.

Base is x = \bold{\</em></strong><strong><em>l</em></strong><strong><em>a</em></strong><strong><em>r</em></strong><strong><em>g</em></strong><strong><em>e</em></strong><strong><em>{\fbox{\color{blue} {</em></strong><strong><em>9</em></strong><strong><em> </em></strong><strong><em>cm</em></strong><strong><em>}}}}

Perpendicular is x+3=9+3 = \bold{\</em><em>l</em><em>a</em><em>r</em><em>g</em><em>e</em><em>{\fbox{\color{</em><em>gree</em><em>n</em><em>} {</em><em>1</em><em>2</em><em> </em><em>cm</em><em>}}}}

Step-by-step explanation:

HOPE IT HELP YOU

Similar questions